2013
DOI: 10.1111/resp.12219
|View full text |Cite
|
Sign up to set email alerts
|

The Sputum Colour Chart as a predictor of lung inflammation, proteolysis and damage in non‐cystic fibrosis bronchiectasis: A case–control analysis

Abstract: We show that sputum purulence assessment in daily clinical practice using the SCC is a quick and easy tool that reflects severity of inflammation, destruction and proteolytic enzymatic activity/presence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
52
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 30 publications
(77 reference statements)
4
52
1
2
Order By: Relevance
“…NE is not the only airway protease found in the bronchiectasis lung, but Goeminne and colleagues, in a study of 63 patients, showed that NE accounted for 82% of the total gelatinolytic activity of sputum, making a greater contribution than matrix metalloproteinases (15). Goeminne and colleagues also showed a statistically significant association between NE and FEV 1 % predicted, which was not seen for matrix metalloproteinase-9 (MMP-9) (15).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…NE is not the only airway protease found in the bronchiectasis lung, but Goeminne and colleagues, in a study of 63 patients, showed that NE accounted for 82% of the total gelatinolytic activity of sputum, making a greater contribution than matrix metalloproteinases (15). Goeminne and colleagues also showed a statistically significant association between NE and FEV 1 % predicted, which was not seen for matrix metalloproteinase-9 (MMP-9) (15).…”
Section: Discussionmentioning
confidence: 96%
“…However, in bronchiectasis, release of NE overwhelms the antiproteinase defense, which leads to detectable levels of NE proteolytic activity in sputum and bronchoalveolar lavage (13)(14)(15). This can be measured readily using assays that detect cleavage of chromogenic or fluorogenic peptide-based substrates in sputum, or downstream by measuring the endogenous degradation of mature elastin through the quantification of the unique covalent cross-linking amino acids desmosine and isodesmosine in serum and/or plasma (circulating desmosine [cDES]) (16,17).…”
mentioning
confidence: 99%
“…Similar to subjects with cystic fibrosis, subjects with bronchiectasis reportedly yield higher levels of airway inflammation (mucus hypersecretion, 27 matrix metalloproteinases, [28][29][30] tissue inhibitor of matrix metalloproteinase imbalance, 30 and neutrophil infiltration 28,[30][31][32] ) compared with healthy subjects, which could be directly reflected by sputum color. [30][31][32] In our study, sputum purulence was increased during bronchiectasis exacerbations (Table E7 in the supplementary materials at http://www.rcjournal.…”
Section: Discussionmentioning
confidence: 82%
“…[30][31][32] In our study, sputum purulence was increased during bronchiectasis exacerbations (Table E7 in the supplementary materials at http://www.rcjournal. com), suggesting greater proteolytic activities because of matrix metalloproteinases release.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, sputum color is one of the clinical criteria that improves specificity of the non-cystic fibrosis bronchiectasis exacerbation definition in children. 19 Moreover, Goeminne et al 20 …”
Section: Discussionmentioning
confidence: 98%